Suicide awareness of japanese family descendants (Acta Scientiarum. Health Sciences, 2014)
This study aimed to comprehend the meaning of suicide for Japanese descendants. This was a qualitative study, based on Grounded Theory, using a structured interview with sixteen questions, digitally recorded. Subjects were ten descendants who were interviewed in 2011. The opinions of the interviewed showed factors of psychological, social and cultural origin involved in suicide, such as: heredity, religion, mental health, personality characteristics and interpersonal relationships, pleasure and pain at work, stigma and consequences of the act on the family. Family without case of suicide showed attitudes of prejudice and judgment, while those with case displayed feelings of pain in their reports. It was concluded that the Japanese rigid culture, personality, interpersonal communication and the way family and work have effects on their behavior are predisposing factors to suicide, as well as the identification of these factors contributes to a better performance of the nurse.